FORMULATION AND EVALUATION OF SINTERED GASTRORETENTIVE TABLETS OF VILDAGLIPTIN USING DESIGN OF EXPERIMENT - JUWERIYA, AYESHA; RATNAMALA, K.V. (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The purpose of the study was to formulate and evaluate sintered gastro retentive tablets of Vildagliptin using the design of experiments. Methods: Direct compression is the process by which tablets are compressed from powder mixture of API and suitable excipients and compression was done by an automatic punching machine using 6 mm punch. Prepared tablets were kept in the hot air oven at three different temperatures of 50°C, 60°C, 70°C for three different periods of 1, 2, 3 h. Results and Discussion: The physiochemical evaluation results of the powder blend of all the trails pass the flow properties and compression properties and are of uniform density (i.e., Angle of repose, Bulk density, Compressibility index, Hausner’s ratio). Among all the Formulations, Formulation F7 showed better results such as Angle of repose F7(29.9), Hausners ratio of F7(1.18), and compressibility index of F7 (15.6) which indicate the good flow properties. The prepared tablets were evaluated for the post compression properties such as thickness, hardness, Weight variation, friability, and drug content found within limits. Each formulation was analyzed spectrophotometric ally, and each formulation showed drug content >80%. Formulation F7 consisting of polymers (stearic acid, carnauba wax) and gum (xanthan gum) showed percentage drug release of 95.8 at 12 h. The developed formulations were optimized by Box Behnken design to achieve desired properties. Conclusion: Vildagliptin has good solubility in acidic pH. It has good absorption from an acidic environment. By preparing floating tablets of Vildagliptin, its bioavailability can be enhanced as more amount drug will be absorbed from stomach. Vildagliptin is having high melting point of 158–160°C which is best suitable for the thermal sintering technique. The aim of the present study to formulate and evaluate Sintered Gastro retentive tablets of Vildagliptin using Design of Expert was successfully achieved.